A Systematic Review of The Trends Research Problem Solving Ability in Physics Learning (2015-2024) - Galuh Elisa Roliana Fatimah; Aris Doyan; Syafrul Annam (Postgraduate Program, University of Mataram, 2024)
21st century learning encourages students to have the ability to solve problems in the learning process. This study aims to explore and assess the trends in research focusing on problem-solving abilities in physics learning. Employing descriptive and analytical methods, the data was sourced from documents indexed by Google Scholar between 2015 and 2024, using Publish or Perish and Dimensions.ai. The research followed PRISMA guidelines, analyzing publication types, sources, and frequently cited titles concerning problem-solving abilities in physics learning. Bibliometric analysis, supported by VOS viewer software, was utilized for data examination. The findings reveal a consistent increase in research on problem-solving abilities in physics education indexed by Google Scholar from 2015 to 2024. This trend indicates that such research has gained significant popularity among both new and experienced researchers. A substantial number of articles, proceedings, book chapters, and edited books address this topic. Common keywords in these studies include the STEM approach, critical thinking, creative thinking, physics problem-solving abilities, conventional learning, authentic assessment, etc.